Getting started with Corel Painter 2016 : learn to use brushes, layers, cloning, and special effects - Draws, Rhoda (O'Reilly, 2016)
"With Early Release video training, you get videos as they're being developed so you can take advantage of these technologies long before the official release of these titles. You'll also receive updates when significant changes are made, new chapters as they're edited, and the final video. In this Getting Started with Corel Painter 2016 training course, expert author Rhoda Draws will teach you everything you need to know about Corel Painter's core tools and features. This course is designed for the absolute beginner, meaning no previous experience with Corel Painter is required. You will start by learning how to work with layers, then jump into learning about the Painter desktop. From there, Rhoda will teach you about clone painting, brush controls, and how to paint a pastel portrait. This video tutorial also covers the effects menu, selection techniques, working with text, and dynamic layers. Finally, you will learn about watercolor and how to create a mixed media portrait. Once you have completed this computer based training course, you will have gained a solid understanding of Painter's core tools and features. Working files are included, allowing you to follow along with the author throughout the lessons."--Resource description page.